A Coarsening Algorithm on Adaptive Grids by the Newest Vertex Bisection and Its Applications (Journal of Computational Mathematics, 2021)
In this paper, an efficient and easy-to-implement coarsening algorithm is proposed for adaptive grids obtained using the newest vertex bisection method in two dimensions. The new coarsening algorithm does not require storing the binary refinement tree explicitly. Instead, the structure is implicitly contained in a special ordering of triangular elements. Numerical experiments demonstrate that the proposed coarsening algorithm is efficient when applied for multilevel preconditioners and mesh adaptivity for time-dependent problems.
Keywords: Adaptive finite element method; Coarsening; Newest vertex bisection; Multilevel preconditioning.